A Multimodel Investigation of Asian Summer Monsoon UTLS Transport Over the Western Pacific. Issue 24 (23rd December 2022) - Pan, Laura L.; Kinnison, Douglas; Liang, Qing; Chin, Mian; Santee, Michelle L.; Flemming, Johannes; Smith, Warren P.; Honomichl, Shawn B.; Bresch, James F.; Lait, Leslie R.; Zhu, Yunqian; Tilmes, Simone; et al.
Abstract: The Asian summer monsoon (ASM) as a chemical transport system is investigated using a suite of models in preparation for an airborne field campaign over the Western Pacific. Results show that the dynamical process of anticyclone eddy shedding in the upper troposphere rapidly transports convectively uplifted Asian boundary layer air masses to the upper troposphere and lower stratosphere over the Western Pacific. The models show that the transported air masses contain significantly enhanced aerosol loading and a complex chemical mixture of trace gases that are relevant to ozone chemistry. The chemical forecast models consistently predict the occurrence of the shedding events, but the predicted concentrations of transported trace gases and aerosols often differ between models. The airborne measurements to be obtained in the field campaign are expected to help reduce the model uncertainties. Furthermore, the large‐scale seasonal chemical structure of the monsoon system is obtained from modeled carbon monoxide, a tracer of the convective transport of pollutants, which provides a new perspective of the ASM circulation, complementing the dynamical characterization of the monsoon. Plain Language Summary: The Asian summer monsoon has been known as a weather system for centuries, but only in the recent decades has the system been recognized for its importance in atmospheric composition. Monsoon deep convection lofts near surface air to 15–17 km altitudes thus altering the chemical composition of the tropopause layer. The process also sends aerosols and chemically active trace gas species into the stratosphere where they affect climate through their impacts on ozone and aerosol radiative forcing. To understand the monsoon transport process and its impacts on climate system, a large airborne field campaign, the Asian summer monsoon Chemical and Climate Impact Project, was planned. This paper presents a set of results from precampaign model studies. These results serve as the hypotheses for the field investigation and provide guidance for its operational planning. Key Points: This model study is conducted in preparation for an airborne field campaign investigating the Asian monsoon transport Result shows that eastward eddy shedding of the anticyclone significantly alters upper tropospheric composition over the Western Pacific CO seasonal distribution provides a chemical perspective of the monsoon system and sheds new light on monsoon dynamics and circulation